RANCANGAN SISTEM PERSEDIAAN BAHAN BAKU MENGGUNAKAN MODEL PERSEDIAAN STOCHASTIC JOINT REPLENISHMENT - Edi Susanto; Dedeng Abdul Gani Amruloh (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2020)
Inventory control of raw material supplies is required for the company to ensure the smoothness of production processes. PT. SEA is a company that is engaged in the manufacture of Al-Quran. The system of the company is still using intuition, by making a separate order on each type of raw material when supplies of raw materials in the warehouse are lacking. Raw material ordering is done without the consideration of other raw materials originating from the same supplier. That resulted in high inventory costs. The right solution according to the problem is to use the stochastic inventory model in the case of joint replenishment. This method generates a combined booking time interval and maximum inventory for each type of raw material. The number of times the company's booking is based on past data is 13 times as much as 5 per year. Resulting in a frequency savings of the booking time of 61.58%. Times. Meanwhile, the savings on the previous stock cost is Rp 989,840,767.50 per year. The total cost of inventory by using the result of the proposal is Rp 982,254,563.75 per year, saving about Rp. 7.586.20375 year or down about 0.7%.